PEMANFAATAN DANA BANTUAN KIPK OLEH MAHASISWA PENERIMA KIPK DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Pasaribu, Ummi Muannur; Supsiloani (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
This research aims to find out how KIP-K aid funds are utilized by KIP-K recipient students at the Faculty of Education, Medan State University in 2020. This research also examines how the KIP-K aid funds are implemented by KIP-K recipient students in Medan State University Faculty of Education. This research was conducted at the Faculty of Education, Medan State University. This research was conducted using qualitative research with observation, interview and documentation methods. The results of this research show that the students who receive KIP-K assistance funds provided by the government are students who truly come from low-income or disadvantaged economies who have met the requirements to be part of the KIP-K recipients. The use and implementation of KIP-K assistance funds that have been carried out by KIP-K recipient students at the Faculty of Education, Medan State University has been appropriate for its use, namely no longer paying tuition fees for a single semester of study, can help meet living needs during lectures and utilize funds KIP-K assistance on matters related to lectures.